Role of AMPK in skeletal muscle metabolic regulation and adaptation in relation to exercise - Jørgensen, Sebastian B (Blackwell Science Inc, 2006)
The 5′-AMP-activated protein kinase (AMPK) is a potent regulator of skeletal muscle metabolism and gene expression. AMPK is activated both in response to in vivo exercise and ex vivo contraction. AMPK is therefore believed to be an important signalling molecule in regulating muscle metabolism during exercise as well as in adaptation of skeletal muscle to exercise training. The first part of this review is focused on different mechanisms regulating AMPK activity during muscle work such as alterations in nucleotide concentrations, availability of energy substrates and upstream AMPK kinases. We furthermore discuss the possible role of AMPK as a master switch in skeletal muscle metabolism with the main focus on AMPK in metabolic regulation during muscle work. Finally, AMPK has a well established role in regulating expression of genes encoding various enzymes in muscle, and this issue is discussed in relation to adaptation of skeletal muscle to exercise training.